A Prospective Study of Villous Capillary Lesions in Complicated Pregnancies - Anu Priyadharshini Srinivasan; B. O. Parijatham Omprakash; Kandhimalla Lavanya; Priyadharshini Subbulakshmi Murugesan; Saraswathi Kandaswamy (Journal of Pregnancy)
The vascularity of placental tissue is dependent on various factors of which fetomaternal hypoxia plays a major role. Hypoxia can be of different types and each type influences the vascularity of the villi, especially terminal villi, in its own way. In this study, we attempted to identify villous vascular changes in a group of term placentae from mothers with diseases complicating pregnancy. Chorangiosis was the most frequently identified lesion while chorangioma was found in only 2 cases. There were no cases of chorangiomatosis. A few cases had normal villous vasculature. Maternal diseases have a major role in disrupting the placental vasculogenesis and angiogenesis by creating a hypoxic environment that may affect the fetus adversely. Hence, such conditions need to be identified early in pregnancy and managed appropriately as it is possible to maintain a normal vasculature and prevent neonatal mortality and morbidity if prompt intervention is done.